VACANCIA PRESIDENCIAL, TRANSICIÓN DEMOCRÁTICA Y OMISIONES CONSTITUCIONALES - Hakansson Nieto, Carlos (Revista de Derecho, 2022)
After four consecutive and democratic elections in Perú, the form of government start to developed several political and academic discussions about the vote of no confidence, parliamentary dissolution, also the causes of interrupt the president during his term. This paper has wanted to explain the meaning, effects, and consequences of theoretical and practice when Congress decides to apply for a presidential vacancy.